The Influence of Influencer Marketing, Electronic Word of Mouth (e-WOM), and Brand Awareness on the Decision to Play Roblox in Mataram City - Adinda Melisa Putri; Akhmad Saufi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of the online gaming industry in Indonesia prompted this study to analyze the influence of influencer marketing, electronic word of mouth (e-WOM), and brand awareness on the decision to play Roblox in Mataram City. The study aims to test the causal relationship between the three independent variables and the dependent variable using a causal associative quantitative approach. The population is the young generation of active Roblox players in Mataram, with a sample of 97 respondents selected purposively (aged 18-25 years). The instrument, a 5-point Likert questionnaire, was tested for validity (r > 0.196) and reliability (alpha > 0.60), analyzed using SPSS multiple linear regression after classical assumption testing. The results showed a significant simultaneous effect (R² = 0.693; F = 69.891, p < 0.05) and positive partial (influencer marketing β = 0.233 p = 0.012; e-WOM β = 0.480 p = 0.000; brand awareness β = 0.313 p = 0.000), with e-WOM being the most dominant. The conclusion states that all three factors effectively drive gaming decisions, different from physical product studies, with implications for regional digital marketing strategies